Effects of adipokinetic hormone/red pigment-concentrating hormone family of peptides in olfactory bulbectomy model and posttraumatic stress disorder model of rats - Mutlu, Oguz; Kurtas, Omer; Kleteckova, Lenka; Pinterova, Nikola; Holubová, Kristina; Horacek, Jiří; Hoschl, Cyril; Uygun, Ibrahim; Rodriguez, Daniel Bermejo; Kacer, David; Muhametaj, Franko; Vales, Karel (Peptides, 2020)
One of the major neuropeptide groups in insects is adipokinetic hormone/red pigment-concentrating hormone (AKH/RPCH) family of peptides. AKH had improving effects on depression and anxiety in animal models and it may be a new treatment choice in these disorders. Aim of this study was to investigate effects of Anax imperator AKH (Ani-AKH), Libellula auripennis AKH (Lia-AKH) and Phormia-Terra hypertrehalosemic hormone (Pht-HrTH) on animal behavior in olfactory bulbectomy (OBX) model and in posttraumatic stress disorder (PTSD) model of Wistar-albino rats. Lia-AKH and Pht-HrTH significantly increased time spent in escape platform's quadrant compared to sham control while Lia-AKH significantly increased time spent in escape platform's quadrant compared to OBX controls in probe trial of Morris water maze (MWM). Ani-AKH, Lia-AKH and Pht-HrTH significantly decreased immobility time compared to OBX controls in forced swimming test (FST). Pht-HrTH significantly increased %open arm time compared to OBX controls in elevated plus maze (EPM) test. Ani-AKH significantly increased %open arm entry compared to sham control while Ani-AKH and Pht-HrTH significantly increased %open arm entry compared to OBX controls in EPM. In PTSD study Ani-AKH and Lia-AKH significantly decreased immobility time compared to traumatized controls in FST. In acoustic startle reflex test, Ani-AKH, Lia-AKH and Pht-HrTH significantly decreased average startle amplitude compared to non-traumatized controls in PTSD study. Metabolomic studies showed that AKH may affect glutamatergic and dopaminergic system and neurochemistry. In conclusion, AKH peptides had wide ranging effects on behavior and improved performance in OBX and PTSD models in rats.
Keywords: Behavior, Animal; Olfactory Bulb; modely nemocí na zvířatech; Male; Rats, Wistar; neuropeptidy; hmyzí hormony; mužské pohlaví; potkani Wistar; bulbus olfactorius; Oligopeptides; kyselina pyrrolidonkarboxylová; Stress Disorders, Post-Traumatic; krysa rodu Rattus; Pyrrolidonecarboxylic Acid; úzkost; Animals; zvířata; posttraumatická stresová porucha; Insect Hormones; Disease Models, Animal; Rats; chování zvířat; oligopeptidy; Anxiety; Neuropeptides